Effect of spinal anesthesia with sufentanil on length of stages I and II of labor in singleton pregnant women: a randomized controlled trial - Mina Yadollahi; Kambiz Sadegi; Batool Shahraki Mojahed (Faculty of Medicine, Universitas Trisakti, 2023)
BackgroundLabor pain is one of the most painful experiences in a women's life. One of the methods of pain relief is spinal anesthesia. The purpose of this study was to evaluate the effect of spinal anesthesia with sufentanil on the length of the first and second stages of labor in singleton pregnant women. MethodsA randomized clinical trial was conducted involving 56 women who had to be at least 37 weeks pregnant with a singleton pregnancy and 20 to 35 years of age, as well as seeking a spontaneous natural delivery. They were randomized into an intervention group (spinal anesthesia with sufentanil) of 28 subjects and a control group (no spinal anesthesia) of 28 subjects. Statistical analysis was performed using SPSS software program 20.0. ResultsMean duration of stage I of labor was 152.32 ± 92.01 and 187.68 ± 121.01 minutes in the intervention and control groups, respectively (p=0.34), whereas mean duration of stage II of labor in the 2 groups was 15.96 ± 14.26 and 26.43 ± 20.90 minutes, respectively (p=0.06). Twenty five percent of women in the intervention group and 35.71% of women in the control group experienced a long stage I, whereas 21.43% of women in the intervention group and 35.71% of women in the control group experienced a long stage II (p>0.05). ConclusionThis study suggests that spinal anesthesia with sufentanil does not increase the duration of labor stages. It is recommended that more studies be performed in the future using larger sample sizes to allow for the drawing of solid conclusions.